Crossrail Project : infrastructure design and construction. Volume 6 - Williams, Rhys Vaughan; Bennett, Simon (ICE Publishing, 2022)
Crossrail Project: Infrastructure Design and Construction Volume 6 contains a collection of 22 papers submitted to the 2021 Crossrail's Technical Papers Competition. Contributions have come from members of the Crossrail organisation, its consultants as well as contractors involved in design and construction across the Crossrail project. The papers cover a multitude of disciplines including tunnelling, geotechnical engineering, rail signalling and control, rail systems & integration, rail telecommunications, and electrical engineering.
Also issued in print: 2022.
Includes index.
Keywords: Railroads -- England -- London -- Design and construction.; Railroads -- Planning -- England -- London.; elektronické knihy; electronic books